Perbedaan Pengaruh Antara Hold Relax Dan Contract Relax Terhadap Peningkatan Lingkup Gerak Sendi Lutut Pada Kondisi Post Fraktur Femur Sepertiga Bawah Dengan Pemasangan Fiksasi Internal - Ambar Kusuma, Septyana, Maskun Pudjianto, SMPh., S.Pd., M.Kes (2016)
PURPOSE: To know the effect of hold relax exercise with the increase of knee's ROM, know the effect of contract relax with the increase of knee's ROM, know the difference effects of hold relax and contract relax excercise with the increase of knee's ROM. BACKGROUND: The incident of the distal shaft fractures of femur will involve the knee joint and quadriceps mechanism or both, so the loss of several knee joint motions can not be circumvented by the installation of most patients with internal fixation. The knee's ROM limitation will give further effect that limitation fungsion of leg. The PNF technic on hold relax and contract relax are one of exercise early method which can be elected at increased flexibility associated with LGS. SUBJECTS: All post surgery patients of the distal shaft fractures of femur at Karima Utama Surakarta Hospital started on September 2 until October 25, 2016. The subject is obtained as many as 20 peoples consisted of 9 female patients and 11 male patients with a range aged between 16 to 58 years old included in inclusion criteria and divided into 2 groups. Group I get treatment with the hold relax exercises method and Group 2 get treatment with contract relax excercise. RESEARCH DESIGN: Two Group Pre and Post Test Design, sample size less than 50 are not taken normality test, later taken different test with Wilcoxon to determine the differences before and after ROM knee treatment in each group and different test with the Mann-Whitney to know the difference effect after treatment in group I and group II with 95% confidence level (p = 0,05), obtained from the subjects taken knee ROM measurement before and after treatment as much as 4 times for 3 days. RESULTS: Different test on ROM of knee joint before and after treatment in group I, pvalue = 0.005 (p ≤ 0.05). different test on ROM of knee joint before and after treatment in group II, p-value = 0.005 (p ≤ 0.05). Different test after treatment in group I and II, pvalue = 0.000 (p ≤ 0.05) From the descriptif data show there is a big difference ROM of the knee joint before and after treatment in each group and there is difference ROM of the knee joint after treatment between groups I and II. CONCLUSION: There is effect of hold relax exercise to increase of knee's ROM, there is effect of hold relax to increase ofknee's ROM, there is difference between hold relax and contract relax to increase of knee's ROM, hold relax exercise is better than contract relax exercise to increase of knee's ROM. Keywords: Fractures of the distal shaft of femur, hold relax, contract relax, and ROM of the knee joint.